Feromoninnehållande substansers effekt på hjärtfrekvensen hos kvigor i östrus och diöstrus - Nordéus, Kristina (SLU/Dept. of Clinical Sciences (until 231231), 2007)
With increased milkproduction in our dairy cattle, comes a risk for a reduced fertility. Studies performed on animals and humans have shown that it is possible to manipulate the oestrous cycle through exposure to pheromones. This means that pheromones could potentionally be used to make reproduction more efficient. To evaluate the bioactivity of the substances in question, there is need for a bioassay. In insects, pheromones can induce a changed cardiac activity. In this study we wanted to examine whether the same also applied to cattle. We monitored three oestrous cycles in two heifers and exposed them to urine from bulls and to vaginal mucus and urine from cows in oestrus, substances thought to contain pheromones, during oestrus and dioestrus. We found that there was no significant change in heart rate due to exposure to pheromones. But we found that, in general, the heart rate was higher during oestrus than during dioestrus. The results show that heart activity seems to be a poor monitor of the effect of substances containing pheromones in cattle. We noticed, however, that during the study the oestrous cycles of the two heifers were somewhat synchronized, which may be caused by pheromones. This implies that further studies regarding the effect of pheromones on the oestrous cycle in cattle are of interest.